The role of brachytherapy in liver metastases from colorectal cancer - Cisek, Paweł; Kordzińska-Cisek, Izabela; Grzybowska-Szatkowska, Ludmiła (Frontiers in Immunology, 2025)
ObjectiveHDR interstitial brachytherapy is one of the non-surgical methods of local treatment of liver metastases. A cancer in which local treatment of liver metastases is particularly important is colorectal cancer. The aim of the present study was to evaluate the efficacy, safety and tolerability of brachytherapy of liver metastases of colorectal cancer.Material and methodsThe analysis included 270 patients with liver metastases from colorectal cancer treated between 2015 and 2022. Patients were divided into 3 groups according to indications for treatment: patients with repeat oligoprogression, induced oligoprogression and induced oligopersistence. Patients were analysed in terms of PFS and OS depending on epidemiological factors such as age and gender and clinical factors such as tumour location, type of metastases, stage, LVSI, degree of malignancy, location of extrahepatic lesions, size of metastases, number of metastases, treatment intention and dose. The degree of response to treatment and its toxicity were assessed.ResultsDuring an average follow-up period of 16 months, the median PFS was 10 months and the OS was 17 months. 6m-, 12m-24m-PFS were 79%, 42% and 2%, respectively. and 6m-, 12m- and 24m-OS were 99%, 74% and 22%, respectively. DCR was 85%, ORR – 35%. 9% had CR, 26% PR, 50% SD, and 14% PD. The most important factors that influenced the prognosis were the intention of treatment, the degree of response to treatment, the dose administered, the presence of extrahepatic metastases, and the degree of malignancy. The toxicity of the treatment was low, and the most common side effect was pain at the injection siteConclusionsBrachytherapy is an effective and safe method of local treatment of liver metastases and should be considered especially in patients with a limited number of metastases who do not qualify for surgical treatment and the size of the metastases prevents the use of stereotactic radiotherapy.